IDENTIFIKASI CEMARAN LOGAM Sn (TIMAH) DALAM SUSU KENTAL MANIS KEMASAN KALENG - Maimunah, Siti; Hafizullah, Ahmad; Simarmata, Yettrie (Jurnal Farmanesia, 2018)
Condensed milk or more commonly sweetened condensed milk is cow's milk in which the water is removed and sugar is added, resulting in milk that is very sweet in taste and can last for up to a year if not opened. In general, the term sweetened condensed milk means sweetened milk, namely milk in the form of a thick liquid, yellowish-white or other colors depending on the aroma added, with a distinctive smell and taste. This research was conducted to determine the presence or absence of metallic Sn (tin) in canned sweetened condensed milk in whole and dented cans. The samples examined were whole and dented canned sweetened condensed milk sold around Jalan Kapten Muslim Medan, the samples were taken randomly from three different brands. This study used a qualitative test method, the sample was ashed first using 0.1N HCl solvent, this research was carried out using 0.1N sodium hydroxide reagent there was no white or negative precipitate, using 0.1N sodium carbonate reagent there was no white precipitate or negative. Sweetened condensed milk sold around Jalan Kapten Muslim Medan does not contain Sn (tin) in the qualitative test, this shows that the sweetened condensed milk is safe for consumption.